The Impact of the One Belt One Road Initiative on the Economy of China - Zhao, Mingyu (2020)
The main purpose of this study is to research the impact of the Belt and Road Initiative on the Chinese economy. Before starting the analysis, the author puts forward two hypotheses for the problems studied in this thesis. First, the Belt and Road transport infrastructure can promote foreign trade. and second, the development of foreign trade has driven the development of China's economy. Then the author's analysis process is as follows. First of all, the Belt and Road Initiative increased China's investment in transportation infrastructure, then the increase of China's transportation infrastructure investment drives the development of China's foreign trade, and finally the development of China's foreign trade drives the development of China's economy. The research data in this thesis are from the National Bureau of Statistics and the Ministry of Transport of China. The author used OLS linear regression method to analyze the related data. In the empirical study of the impact of foreign trade on China's economy, the author was inspired by Balassa (1978) and expanded the Cobb–Douglas production function. Then the results show that there is a positive correlation between transportation infrastructure and import and export trade, and also there is a positive correlation between foreign trade and China's economic development. This means that the increase of transport infrastructure investment can have a positive effect on economic growth by affecting import and export trade. Finally, the author suggests that China should continue to invest in transportation infrastructure, especially in highway, waterways and pipeline construction.